Leadership : theory and practice Ed 9 - Peter G Northhouse (Los Angeles Sage, 2022)
The market-leading Leadership: Theory and Practice presents an academically robust account of the major theories and models of leadership with a focus on how theory can inform practice. Author Peter G. Northouse uses a consistent structure for each chapter that allows readers to easily compare and contrast different theories. Case studies and questionnaires provide students with practical examples and opportunities to deepen their understanding of their own leadership style. The fully updated Ninth Edition features a new chapter on inclusive leadership, 17 new real-world cases that profile leaders from across the globe, a new discussion on leadership and morality, and examples of timely issues such as leadership during the COVID-19 pandemic.
Keywords: Transformational Leadership; Leadership Ethics; Team Leadership; Authentic Leadership